Ancient Hybridization with an Unknown Population Facilitated High-Altitude Adaptation of Canids. (11th May 2020) - Wang, Ming-Shan; Wang, Sheng; Li, Yan; Jhala, Yadvendradev; Thakur, Mukesh; Otecko, Newton O; Si, Jing-Fang; Chen, Hong-Man; Shapiro, Beth; Nielsen, Rasmus; Zhang, Ya-Ping; Wu, Dong-Dong
Abstract: Genetic introgression not only provides material for adaptive evolution but also confounds our understanding of evolutionary history. This is particularly true for canids, a species complex in which genome sequencing and analysis has revealed a complex history of admixture and introgression. Here, we sequence 19 new whole genomes from high-altitude Tibetan and Himalayan wolves and dogs and combine these into a larger data set of 166 whole canid genomes. Using these data, we explore the evolutionary history and adaptation of these and other canid lineages. We find that Tibetan and Himalayan wolves are closely related to each other, and that ∼39% of their nuclear genome is derived from an as-yet-unrecognized wolf-like lineage that is deeply diverged from living Holarctic wolves and dogs. The EPAS1 haplotype, which is present at high frequencies in Tibetan dog breeds and wolves and confers an adaptive advantage to animals living at high altitudes, was probably derived from this ancient lineage. Our study underscores the complexity of canid evolution and demonstrates how admixture and introgression can shape the evolutionary trajectories of species.